Modelling in Development of Safety-Related Communication Systems - Karol Rastocny; Maria Franekova (Communications - Scientific letters of the University of Zilina, 2008)
The aim of the paper is the use of modelling within development of safety–related communication systems presented in the areas where guaranty of asafety integrity level is required. The basic principles and standards used in the process of safety evaluation in closed transmission systems are summarised in the paper. Dangerous states of the system are mainly caused by systematic failures within aspecification of the system, electromagnetic disturbance and random failures the HW effects. The main part of the paper describes the safety analysis process on the example of the end to end closed transmission system with the use of the fault tree and Markov’s chain.